A study on the investigation of the biomarker potential of miRNA-21 expression in colorectal tumor samples and serum - Kalariya, Bhargav J.; R. D. R., Arul Jothi; S., Sumanth; S., Guruprasath (International Surgery Journal, 2024)
Background: miRNAs have been highlighted as diagnostic, prognostic, and predictive biomarkers because of the high tissue specificity, stability and altered expression in tumor development. miRNA analysis could offer a less invasive and more cost-effective alternative to supplement existing screening approaches. Methods: All colorectal cancer patients were subjected to serum miR21 expression and from biopsy by RT PCR. Results: Higher stage tumors had higher expression of miR21 in both serum and biopsy. Higher grade tumors had higher expression of miR21 in both serum and biopsy. Conclusions: From our study, we conclude that, Higher miRNA 21 expression in serum and biopsy were associated with acute presentations and advanced stages of colorectal malignancies. Serum miRNA 21 expression patterns can be found even in early-stage malignancies of colorectal tumors, hence serving as a useful noninvasive biomarker. miRNAs have been highlighted as diagnostic, prognostic, and predictive biomarkers because of the high tissue specificity, stability, and altered expression in tumor development. Thus, miRNA21 analysis could offer a less-invasive and more cost-effective alternative to supplement existing screening approaches.